Exploring the Teachers and Learners’ Perceptions of Online Corrective Feedback through Multiple Platforms - Ris Suliandari; Ahmad Zamzam; Khusnul Khotimah (Research And Innovation In Language Learning (RILL), 2022)
The shift to online learning milieu due to the Covid-19 pandemic has brought some impact in the practices or teaching learning including the nature of writing corrective feedback (WCF) that should also be migrated to online platforms. Although much research has been conducted on the effectiveness of WCF, less has explored student and teacher preferences and perceptions of online corrective feedback through various platforms in student thesis writing in response to this abrupt learning transformation. Lensing from a case study, we recruited two English teachers and fifteen learners non-randomly with a purposive sampling technique. This study used closed-ended questionnaires and semi-structured interviews. In analyzing the data, the researchers used the formulation of Sudijono (2006) for a closed-ended questionnaire and adapted the steps formulated by Creswell (2003) to analysis the interview data. The result showed that there were differences in preferences and perceptions between teachers and learners regarding the use of different types of WCF: direct and indirect feedback. The teachers prefer to use both types of feedback: direct and indirect feedback. Meanwhile, learners preferred direct corrective feedback. Thus, some pedagogical contribution is also discussed, accordingly.